Answer:
x= -15 or (7x+5)
Step-by-step explanation:
Simplifying
4x + 10 = 3x + -5
Reorder the terms:
10 + 4x = 3x + -5
Reorder the terms:
10 + 4x = -5 + 3x
Solving
10 + 4x = -5 + 3x
Solving for variable 'x'.
Move all terms containing x to the left, all other terms to the right.
Add '-3x' to each side of the equation.
10 + 4x + -3x = -5 + 3x + -3x
Combine like terms: 4x + -3x = 1x
10 + 1x = -5 + 3x + -3x
Combine like terms: 3x + -3x = 0
10 + 1x = -5 + 0
10 + 1x = -5
Add '-10' to each side of the equation.
10 + -10 + 1x = -5 + -10
Combine like terms: 10 + -10 = 0
0 + 1x = -5 + -10
1x = -5 + -10
Combine like terms: -5 + -10 = -15
1x = -15
Divide each side by '1'.
x = -15
Simplifying
x = -15